PENGENALAN GAYA BELAJAR UNTUK EFEKTIVITAS PENDAMPINGAN BELAJAR ANAK DI DESA DURUNG BEDUG - intan bigita kusumawati (STKIP PGRI Sidoarjo, 2018)
Introductory learning style seminars for the effectiveness of child learning assistance community service program in Durung Bedug is aimed to overcome the problems of most parents who have difficulty in assisting children when learning. This activity plan is done in 3 stages. In the first stage, observation is carried out on the program objectives to determine the method of delivering the seminar in accordance with the target condition and situation. In addition, coordination with village officials for administration as well as preparing various things related to activities. In the second phase of the implementation phase, the delivery of materials on learning styles on the target. At the ending stage, follow-up activities are in the form of consultation or follow-up guidance for parents who want to deepen their knowledge about learning style. The results of this activity can be said to be success because of the positive responses of participants during and after the seminar and also the increase of learning outcomes of the participant of the seminar after being given a learning coaching seminar according to the learning style.